Insulinoma - review of characteristics, diagnosis and treatment - Sapuła, Klaudia; Remjasz, Klaudia; Siedlecki, Wojciech; Fabiś, Mateusz; Kuchnicka, Julia; Aleksandrowicz, Jakub; Zielińska, Martyna (Journal of Education, Health and Sport, 2022)
Introduction and purpose: Insulinoma is one of a group of pancreatic neuroendocrine neoplasms (NENs). This tumor has its origin in the β cells of the pancreatic islets, which are responsible for the production of insulin. Excessive amounts of this hormone in the body manifest hypoglycemic neuroglycopenic and sympathetic-overstimulation symptoms. The purpose of this review is to analyze information on the characteristics, diagnosis and treatment of patients with insulinoma. Material and methods: This review was based on available data collected in the PubMed database and published between 2017 and 2022. The study was conducted by reviewing keywords as follows: "insulinoma," "NEN," "diagnosis," and "treatment." Results: The diagnosis of insulinoma consists of a typical clinical presentation, biochemical test results indicating hyperinsulinemic hypoglycemia, and presence of a tumor. The treatment targets solutions leading to a complete recovery, usually performing open surgery involving enucleation of the tumor. Conclusions: Despite the characteristic clinical picture, insulinoma is still often a diagnostic problem. It is necessary to work towards improving diagnostic methods and conduct further research into the most effective methods of treating insulinoma.